2007
DOI: 10.12930/0271-9517-27.1.4
|View full text |Cite
|
Sign up to set email alerts
|

The Trickle-Down Effect of Institutional Vision: Vision Statements and Academic Advising

Abstract: A description of the kinds of educated humans to be cultivated at a particular institution can be found in the college or university vision statement. The extent that vision is reflected in the governing models of advising operations, known by personnel, and transformed into day-to-day activities was assessed through a NACADA membership survey. Findings suggest a significant disconnect between the lofty educational aspirations and priorities stated in vision statements and the pragmatics of academic advising o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2010
2010

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Unfortunately, the literature has suggested that expressions of institutional vision tend to be both physically inaccessible to students on most campuses and perceived by many academic advising supervisors to be incompatible with the school's educational aspirations and priorities (Abelman et al, 2007). Advisor supervisors found that visionary conceptions of educational outcomes, student connectedness and engagement, and the manner by which the institution monitors and facilitates academic excellence are detached from the reality of advising operations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Unfortunately, the literature has suggested that expressions of institutional vision tend to be both physically inaccessible to students on most campuses and perceived by many academic advising supervisors to be incompatible with the school's educational aspirations and priorities (Abelman et al, 2007). Advisor supervisors found that visionary conceptions of educational outcomes, student connectedness and engagement, and the manner by which the institution monitors and facilitates academic excellence are detached from the reality of advising operations.…”
Section: Discussionmentioning
confidence: 99%
“…A nation-wide survey of advising supervisors at NACADA-member colleges and universities (Abelman, Atkin, Dalessandro, Snyder-Suhy, & Janstova, 2007) showed that most respondents are familiar with their institution's vision statement and believe that it should serve to guide the development of general advising models, specific operating policies and procedures, and advisor training. However, many supervisors perceive a significant disconnect between the educational aspirations and priorities stated in the vision statements and the pragmatics of academic advising activities.…”
Section: Abstract: Computerized Content Analysis Diffusion Of Innovmentioning
confidence: 99%
See 2 more Smart Citations
“…To this end, the following research questions are posed: The literature on the diffusion of innovations suggests that the nature of the institution's social system-in particular, the size and complexity of its infrastructure-infl uences what is perceived to be innovative (see Rogers, 2004;Wejnert, 2002) and, thus, whether or not that innovation will be accepted, adopted, and relayed to others. Similarly, it has been suggested that an academic community's awareness of and access to any formal declarations by its leadership may be a function of the nature of the institution (Abelman, Atkin, Dalessandro, Snyder-Suhy & Janstova, 2007;Rozycki, 2004;Velcoff & Ferrari, 2006). This includes the size of its student enrollment (see Kuhtmann, 2004), its academic mission (e.g., highest degree granted; see Ayers, 2002;Baldwin, 2005) and its mode of operation (e.g., public or private; see Boerema, 2006;Bryson, 2004).…”
Section: The Verbiage Of Institutional Visionmentioning
confidence: 99%